Influences of residual stress and micro-deformation on microstructures and mechanical properties for Ti-6.5Al-3.5Mo-1.5Zr-0.3Si alloy produced by laser powder bed fusion. (10th June 2021) - Zhang, C.C.; Wei, H.L.; Liu, T.T.; Jiang, L.Y.; Yang, T.; Liao, W.H.
Abstract: Laser powder bed fusion (LPBF) yields unique advantages during the fabrication of titanium alloys. In the present work, Ti-6.5Al-3.5Mo-1.5Zr-0.3Si alloy specimens with excellent mechanical performances were fabricated by LPBF. The as-built specimens displayed relatively high strength and ductility under modest volume energy densities (VEDs), whereas they manifested high strength with low ductility under high VEDs. To investigate the key reason of this phenomenon, the specimens were designed with two VEDs ranges of 60 J/mm 3 and 85 J/mm 3 . Special attention was paid to the influences of residual stress and micro-deformation on microstructures and mechanical properties for the first time. The results indicated that the residual stresses and relative density of the 60 J/mm 3 range specimens were higher than that of the 85 J/mm 3 range specimens. Dislocation multiplication and dislocation movement promoted by the residual stress were hindered by the initial α' phase grain boundary (prior-α'GB ), leading to the formation of α' metastable structures. The mean tensile strength and elongation of the 60 J/mm 3 range specimens were 1248.1 MPa and 12.3 %, respectively, whereas the corresponding values for the 85 J/mm 3 range specimens were 1405.3 MPa, 5.0 %, respectively. During deformation, the strength and ductility of the specimens were first improved by lamellar structures generated from prior-α' phases, and then effectively enhanced by the interaction between the 10–12 twins and dislocations. However, pores significantly reduced the ductility; hence, high VED specimens with large twins and numerous large pores increased the strength and reduce the ductility.